Fritz Jahr’s Bioethical Imperative - Zagorac, Ivana (Array, 2011)
It seems that the revitalisation of Fritz Jahr’s thought has come just at the right time. During the course of its rapid development, bioethics managed to assume different forms, but also to become both reduced in its underlying intention and hyper-specialised in its theoretical and practical aspects. Summed up in his bioethical imperative, Fritz Jahr’s thought prompts us to re- examine both its underlying intention and its field of interest. Accordingly, this paper centres on Jahr’s bioethical imperative, its origins, construction and implications, aiming to scrutinise Jahr’s original thought and his message within the contemporary discourse on bioethics in general and that on integrative bioethics in particular. The latter is examined only in its outlines, leaving room for a possible upgrade. Lastly, the paper looks at the Rijeka Declaration on the Future of Bioethics as a document that represents an attempt to both conceptually and methodologically transform contemporary bioethics within the context of Jahr’s thought.